MATERIAL REQUIREMENT PLANNING CASE STUDY OF DONAT MADU CIHANJUANG BATUSANGKAR - Wartami, Ahmad Fadel; Handayati, Yuanita (Journal of Business and Management, 2018)
Abstract. Inventory management is an important component amongst the most vital segments in operation management, as this zone has been a central management function in material management system. It is likewise a crucial aspect of management, since stock is one of the significant financial assets of a business that can in indirect way influence profitability. This study chose Donat Madu Cihanjuang Batusangkar to be the example case study because this shop doesn’t have any inventory management. The study is done to give suggestion to the manager on the inventory management fit to the shop condition. This study is done using forecasting method and MRP. The objective is to decide which forecasting method and inventory method is the most fitting to be used in Donat Madu Cihanjuang Batusangkar. The forecasting method this study use is Moving Average, Exponential Smoothing, Holt’s Model, and Winter’s Model technique. For the inventory management, the study use Material Requirement Planning by comparing two lot sizing techniques which is Economic Order Quantity (EOQ) with Reorder-point and Lot-for-Lot. The study is starting with forecasting the demand for five months historical data. The demand forecasted is in the period of days. After forecasting then the study proceeds to do Material Requirement Planning using the three lot sizing techniques. The result from comparing all four of the forecasting techniques is that the forecasting technique Winter’s Model is giving the lowest error compared to the other three. While between the two techniques, the Economic Order Quantity is giving lower cost. Based on the observation and the analysis, researcher then recommend starting using inventory management, if possible the one the researcher did in this study. And also, researcher suggest the shop to save the historical data be it demand, ordering, or finance data, as it will possibly be helpful in the continuation of the shop in the future.Keyword: Inventory, Forecasting, Material Requirement Planning, Raw Material